ANALISIS MINAT DAN PARTISIPASI SISWA SDN KWADUNGAN LOR DALAM PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN - Alik Nur Kholis (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to analyse students‘ interest and participation in learning Physical Education Sports and Health and analyse the level of students’ participation in pjok learning activities at SDN Kwadungan Lor.This research uses a phenomenological approach, and the author uses descriptive research methods. The population in this study were all students of SDN Kwadunagn Lor. The sampling technique used is saturated sampling technique, which obtained the sample of this study is class 4 and 5 students of SDN Kwadungan Lor, totalling 21 students. The data analysis technique used in this research is descriptive analysis using percentages.